Pile foundation in karstic limestone terrain: a geotechnical constraint and its solution - Shrivastava, Alok Kumar; Craig, Derek John; Sharma, Maunsell; Zakaria, S. B. (Journal of Nepal Geological Society, 2001)
ABSTRACT The karstic limestone terrain poses complex geotechnical problems, as there are many uncertainties in terms of position and dimension of cavities, sinkholes, pinnacles, and overhangs developed in it. The study deals with the 6.5 km long Ampang Kuala Lumpur Elevated Highway over the rivers Kelang and Ampang in Malaysia. The large-diameter bored piles and cast in-place piles were constructed for this purpose. The toll plaza area is underlain by karstic limestone. In that area, the piles were located in rows extended as columns connected by crosshead whereas they were provided in pile groups of 2, 3, 4, or 5 connected by a rigid pile cap elsewhere. An instrumented test pile was load tested using static method and calibrated with site investigation results. To design the friction piles and end bearing piles, direct methods (viz. exploratory drilling and rock probes) and indirect methods (viz. resistivity survey and transient electromagnetic survey) were adopted. Based on lithologs, the piles were designed using the safety factor of 2 and 3. The rock probe results were used for designing the rock socket length of the end bearing piles. There was much variation between the designed and encountered rock head levels as revealed during the time of excavation. In such cases, the geotechnical design of end bearing piles was reviewed. As in most of the cases, rock probe holes were inclined (as they slid over a rock cliff, overhang, or pinnacle) giving rise to wrong information of rock head levels. To solve this problem at site, a new integrated approach was evolved considering the 3D subsurface topography of rock head level of the area, position and dimension of karstic features, rock mass classifications, and bearing capacity calculation. Based on the above parameters and other measures (underpinning, micropiling, grouting etc.), the piles were designed and load tested.